133k views
2 votes
Given the expressions below, which of the following correctly solves for A + B and B - A?

A: 3X - 2

B: -6X - 7

The answers are in the image

Given the expressions below, which of the following correctly solves for A + B and-example-1
User SeDav
by
7.3k points

1 Answer

4 votes
If you would like to calculate A + B and B - A, you can do this using the following steps:

A = 3 * X - 2
B = - 6 * X - 7

A + B = (3 * X - 2) + (- 6 * X - 7) = - 3 * X - 9
B - A = (- 6 * X - 7) - (3 * X - 2) = - 9 * X - 5

The correct result would be B.
User Trez
by
7.8k points